ANALISIS PENGGUNAAN MEDIA PEMBELAJARAN DARING OLEH DOSEN SELAMA MASA PANDEMI COVID 19 DI POLTEKKES TANJUNGKARANG TAHUN 2021 2022 - Apriyani, Heni; Taufiq, Ihsan; Mariani, Rina (Poltekkes Kemenkes Malang, 2023)
The global pandemic due to the COVID 19 virus has an impact on all society and in various fields including the world of health education. Circular Letter Number 4 of 2020 from the Indonesian Ministry of Education and Culture, since March 2020 learning has been carried out online. Online learning has several advantages, namely not being limited by distance, preventing the transmission of the Covid 19 virus, facilitating interaction between lecturers and students, and quickly accessing information. However, there are also disadvantages to online learning, namely a good internet signal is required, an adequate smart device or laptop is required, the lecturer's explanations are difficult to accept because they do not meet in person. nline learning is inseparable from the learning media used. This study aims to determine the use of online learning media by lecturers at the Tanjungkarang Health Polytechnic and its analysis. The research design was descriptive, with a population and sample of all lecturers at the Tanjungkarang Health Polytechnic, but 94 of the 150 lecturer population 62.67 Percent were willing to become respondents. The measuring tool uses a questionnaire via Google Form. The results showed that Zoom Meeting and Whatsapp Groups were mostly used by respondents. The majority of respondents distributed lecture material in the form of Power Point 88.3 Percent , 21 respondents 22.3 Percent used electronic learning media and 43 respondents 45.7Percent used You Tube as a learning medium.